A new antiplasmodial sterol from Indonesian marine sponge, Xestospongia sp. Issue 6 (19th March 2021) - Murtihapsari, Murtihapsari; Salam, Supriatno; Kurnia, Dikdik; Darwati, Darwati; Kadarusman, Kadarusman; Abdullah, Fajar Fauzi; Herlina, Tati; Husna, Muhammad Hafiz; Awang, Khalijah; Shiono, Yoshihito; Azmi, Mohamad Nurul; Supratman, Unang
Abstract: A new antimalarial sterol, kaimanol (1 ), along with a known sterol, saringosterol (2 ) was isolated from the Indonesian Marine sponge, Xestospongi a sp. The chemical structure of the new compound was determined on the basis of spectroscopic evidences and by comparison to those related compounds previously reported. Isolated compounds, 1 and 2 were evaluated for their antiplasmodial effect against Plasmodium falciparum 3D7 strains. Compounds 1 and 2 exhibited antiplasmodial activity with IC50 values of 359 and 0.250 nM, respectively. Abstract :